The idea of sociogenesis of affective structures in modern philosophy and its psychoanalytic premises - Utiuzh, I. G.; Sajtarly, I. A.; Pavlenko, N. V.; Утюж, Ірина Геннадіївна; Павленко, Нателла Валеріївна (My University, 2020)
The article presents a comparative analysis of both research in psychoanalytic philosophy and some philosophic strategies in the context of socio-cultural interpretations (‘reading’) of human feelings. In solidarity with the ‘philosophy of life’, in the framework of these studies, the existence of mental structures dependent on social circumstances and cultural tradition was proved. Therefore, human immanence should be regarded as a phenomenon largely caused by sociocultural experience, that is immutable, rather than as an ‘autonomous entity’. In other words, these studies are based on the idea of ‘sociogenesis’ of human feelings or so-called doctrine of ‘genealogy of the subject’. This is relevant not only to some sociocultural determinants, but also to the issue of possible psychic genesis, including ‘sociogenesis’ of human aggressiveness.
Keywords: aggressiveness; affective codes; mental structure; psychoanalytic philosophy; passionate love; sociogenesis